Warning system for ethic of visitor in hospital ICU using vision system - Nurul Farah Ain, Abdul Hamid (2012)
A warning system using vision system for ethic of visitor in hospital ICU (Intensive Care Unit) is developed. This system will enable the ICU’s guard monitors the movement of visitor who entered patient’s room at ICU without followed the correct order path. The order path that have been set where: area 1 was a door which the first area this system will detects the moving object, area 2 represented sink area and lastly area 3 represented the patient’s room. To overcome this problem, currently this system will be trained to detect and track moving object in the observation scenes using static camera. This is done with the camera as a vision sensor and area of ICU room will be display. Then, it will sent data to the computer for the image processing process. Based on video processing using MATLAB software and apllications, it consists of four main stages, namely: moving object detection and tracking, analysis of sum of pixels on the set area, interfacing with GUI (Graphical User Interface) and warning system activation. This system will notifies the ICU’s guard in making sure that the visitor will follow the correct path before entering the patient’s room.